Problem of Low Yield In Some Indian Soils - Rai, M.M. (Journal of Soil and Water Conservation, 2022)
The crop yields of different crops like wheat, paddy, Pigeon Pea ( Cajanus cajan L. ), Kodo Millet (Paspalum Scrobiculatum L.) Juar (Sorghum vulgare Pers), Gram (Cicer arietinum L.) etc. grown in tracts near Rewa, Madhya Pradesh, India have been unusually poor. The cause of poor yields of crops in this region has been commonly believed to be the alkalinity or salinity of the soils. A systematic study of some of the soils from this area transported to U.S.A. shows clearly that poor yields are not due to salinity or alkalinity but are due to fertility pro-blems, specially nitrogen and phosphorus.